Thirty-five years of ISLA on form-focused instruction: A meta-analysis. (July 2019) - Kang, Eun Young; Sok, Sarah; Han, ZhaoHong
This meta-analysis offers a snapshot of thirty-five years (1980–2015) of research on instructed second language acquisition (ISLA). Fifty-four empirical studies involving a total of 5, 051 second language learners – sampled from six applied linguistics journals, Applied Linguistics, Language Learning, Language Teaching Research, The Modern Language Journal, Studies in Second Language Acquisition, and TESOL Quarterly – were aggregated for the effects of second language (L2) instruction, yielding an overall large effect size, g = 1.06, 95 % CI = 0.84−1.29. Data were further analysed to identify factors that can modulate the efficacy of instruction. While a minor difference was detected between explicit and implicit instruction, statistically significant effects were found for modes of outcome measures, learners' onset L2 proficiency, research settings, and intensity of instruction.